Extramitochondrial cardiolipin suggests a novel function of mitochondria in spermatogenesis - Ren, Mindong (J Cell Biol, 2019)
Mitochondria contain cardiolipin (CL), an organelle-specific phospholipid that carries four fatty acids with a strong preference for unsaturated chains. Unsaturation is essential for the stability and for the function of mitochondrial CL. Surprisingly, we found tetrapalmitoyl-CL (TPCL), a fully saturated species, in the testes of humans and mice. TPCL was absent from other mouse tissues but was the most abundant CL species in testicular germ cells. Most intriguingly, TPCL was not localized in mitochondria but was in other cellular membranes even though mitochondrial CL was the substrate from which TPCL was synthesized. During spermiogenesis, TPCL became associated with the acrosome, a sperm-specific organelle, along with a subset of authentic mitochondrial proteins, including Ant4, Suox, and Spata18. Our data suggest that mitochondria-derived membranes are assembled into the acrosome, challenging the concept that this organelle is strictly derived from the Golgi apparatus and revealing a novel function of mitochondria.